(untitled) (Huellas, 2020)
The present work gathers some analyses and discussions that the author presented in recent years in various conferences and courses designed for teachers, researchers, graduate, undergraduate and postgraduate students of the National Universities of the Northeast (UNNE), Southern Patagonia (UNPA) and Catamarca (UNCa) in Argentina and the Pedagogical and Technological University of Colombia (UPTC). The purpose of this work is to contribute to the diagnosis of the configuration of the world today and the transformations made evident by geographical spaces, with the intention of resignifying the role of geography and that of its makers in a highly dynamic context. In this sense, some of the author’s own analysis, evaluations and reflections are considered, as well as others borrowed from prominent thinkers, who contribute valuable ideas, perceptions, concerns and worries about the state of the geography and the existing perspectives to face the changes that occur in the discipline and those that will inevitably happen in the coming years.